An optimal matching strategy for screw compressor for heat pump applications. (5th March 2018) - Wang, Yu; Wang, Zhiwei; Li, Mingzhu; Chen, Tingting; Wang, Zhanwei
Highlights: An optimal matching strategy for heat pump (HP) units applications was proposed. An index was introduced to represent the actual energy efficiency of the HP unit. The actual energy efficiency of the HP unit was improved significantly. Abstract: An optimal matching strategy for screw compressor for heat pump (HP) applications was proposed in this study. The strategy focuses on the optimal matching between the built-in volume ratio (BVR) of screw compressors and the annual cooling and heating load demands. A performance index, the annual integrated coefficient of performance under actual operating conditions ( ACOP A ), was introduced to represent the actual operational energy efficiency of the HP unit. The optimization mathematical model and generic framework of the optimal matching strategy were developed. The proposed strategy was applied to a ground-source HP unit to assess its performance. The results show that the optimal matching strategy improved the ACOP A by 6% at most, compared to the conventional matching method on BVR.